Peace over Justice: The Acholi Religious Leaders Peace Initiative (ARLPI) vs. the International Criminal Court (ICC) in Northern Uganda - Apuuli, Kasaija Phillip (Studies in Ethnicity and Nationalism, 2011)
In July 2006, peace talks between the rebel group of the Lord's Resistance Army (LRA) and the government of Uganda opened in the Southern Sudan town of Juba. Since the start of the armed rebellion of the LRA in 1987, these talks presented the most important opportunity to end this armed confrontation in northern Uganda. The LRA rebellion is a continuation of the various rebellions mounted by people in northern Uganda to challenge the capture of power by President Yoweri Museveni and his National Resistance Army (NRA) in 1986. Between 1988 and 2008, peace talks were held between the government and various rebel groups in northern, eastern, central, west Nile, as well as western regions of Uganda to end the insurgencies. Whilst some of the armed rebellions were ended successfully with the signing of peace agreements,1 the LRA rebellion has persisted. This essay discusses the interface between civil society activities and opinions in ending the violent conflict in northern Uganda, and the International Criminal Court (ICC) investigation of the Uganda situation. Civil society, whilst acknowledging the importance of the ICC, has at the same time argued that the Court's pursuit of prosecutorial justice in northern Uganda should take a back seat until positive peace has been achieved. Also, civil society representatives have argued that what northern Uganda needs is restorative rather than retributive justice. Even when the LRA leaders failed to sign the peace agreement in 2008, civil society groups have continued to argue that peace should be achieved before justice by the ICC (or any other institution) is instituted. In December 2003, the government of Uganda and the ICC concluded an agreement for the latter to open an investigation into the situation in northern Uganda with a view to indicting those LRA elements who had perpetrated egregious crimes during the armed rebellion since 1987. In October 2005, the ICC issued arrest warrants for five LRA commanders including its leader, Joseph Kony. Kony and his commanders were charged with various counts of crimes against humanity, including inter alia sexual enslavement, rape, and murder; and war crimes including inter alia enlisting children, pillaging, and murder (Apuuli 2006). When peace talks opened in Juba in 2006, the warrants became a sticking point impeding the conclusion of the final peace agreement, with the LRA representatives arguing that the group would not conclude a peace agreement when the warrants were ‘hanging around the necks’ of their commanders. In response, the government of Uganda argued that it would ask the ICC to withdraw them after the conclusion of the agreement. Meanwhile, throughout the duration of the conflict, civil society groups2 in northern Uganda, particularly the Acholi Religious Leaders Peace Initiative (ARLPI), argued for the peaceful conclusion of the conflict. In fact, on a number of occasions, the group led peace missions to talk to the rebels with a view of persuading them to lay down their arms peacefully. Thus when the ICC entered the fray, the ARLPI argued that the Court would complicate the situation. Whilst recognising the role of the ICC, the ARLPI argued that the institution should take a step back until peace was first realised. The group advanced a number of arguments against the ICC investigation including: that the institution's intervention was one-sided, as it ignored the crimes perpetrated by government forces; that the involvement jeopardised peace negotiations, which had been held on and off since the beginning of early 1990s; that the intervention interfered with the Amnesty Act of 2000; and that the intervention went against the traditional Acholi methods of conflict resolution. Thus, the argument of the group was that peace should come before justice.